Sexual and Reproductive Health and Right Interventions: A Systematic Review - Cherlys Tin Lutfiandini; Retno Indarwati; Praba Diyan Rachmawati (Universitas Nahdlatul Ulama Blitar, 2026)
The interventions are regarding SRHR in different countries vary greatly. Sexual and reproductive health and rights (SRHR) are important components to ensure that young people are able to prevent pregnancy, prevent sexually transmitted diseases and utilize health services. The aim of this systematic review is to analyze interventions that have been provided to adolescents about sexual and reproductive health problems in various countries. The authors conducted a systematic review of research examining interventions to improve sexual and reproductive health at ages 10-35 years using systematic review and meta-analysis (PRISMA) guidelines. Articles used from 2018 to 2023 database in Scopus, Science Direct, Sage Journal, and Pubmed. The authors screened titles and full texts so that data was extracted and analyzed using a practice-based narrative synthesis approach. The search produced 223 results by entering the keywords